Performing and narrating the Tanzanian nation - (:unkn) unknown (My University, 2011)
In Tanzania, the Ujamaa-bashing of the 1980s was prejudicial to the iconic image of the wise Mwalimu that enthusiastic leftist intellectuals propagated abroad and the Tanzanian state diffused in the country. Yet, since his death on October, 14 1999, the relegation of Julius Nyerere from the political landscape has been suddenly inverted. Nyerere is now constituted as a trope through which the Tanzanian nation is constantly remembered, narrated and revivified.Every 14th October, now a public holiday (Nyerere Day), official ceremonies are held nationally to commemorate the death of the first President of Tanzania, Julius Kambarage Nyerere. In the main cities of the country, local, regional and national politicians from across the political spectrum pay tribute to Nyerere in hagiographic speeches praising his personal qualities and highlighting the moral values upon which he built his political vision and the nation’s destiny. That same day, the media is instrumental in propagating a laudatory official memory of Nyerere as special TV and radio programmes as well as extensive supplements in the national newspapers recall his personal trajectory, moral convictions and political choices; broadcast or reprint archives of his speeches and interviews; discuss his political philosophy and legacy; and applaud his role and influence in nation-building to better brandish him as an acclaimed symbol of humility, integrity and incorruptibility in the face of today’s corrupt economic and political elite.
Keywords: African Research